Comparison of marginal adaptation and internal fit of monolithic lithium disilicate crowns produced by four CAD-CAM systems - Ferrairo, Brunna Mota (2016)
Statement of the problem. The marginal adaptation and internal space of monolithic crowns are essential items for their longevity. With the variety of CAD-CAM systems available, evaluating the accuracy of its production is of great clinical interest. Purpose. Evaluating the marginal adaptation and internal fit of monolithic lithium disilicate crowns produced by four different CAD-CAM systems. Material and methods. CAD-CAM systems were selected: Ceramill (Ceramill Motion 2), Cerec (Cerec 3), EDG (CAM5-S1 SmartDent) and Zirkonzahn (M5 Heavy). An artificial lower first molar was prepared for a full crown, duplicated in plaster, scanned and the crown was designed following standardized parameters. Ten lithium disilicate crowns (IPS e.max CAD) per group were milled. The crowns were filled with low viscosity silicone and seated on the prepared tooth. The pellicle formed was scanned by the SkyScan 1076 micro-CT system and subsequently embedded in heavy body silicone, sectioned and captured by means of a stereomicroscope at 50x magnification, according to replica technique. Internal and marginal adaptation were measured in the micro-CT and in stereomicroscope images. Two-way ANOVA followed by Tukeys test were used for statistical analysis (=.05). A uniformity index (UI) to describe the internal space of the crown was idealized and submitted to the Kruskal-Wallis one-way analysis of variance on ranks and Tukeys test (=.05). Results. Marginal adaptation presented values ranging from 48,2 ± 19,6 m to 133,0 ± 71,5 m. Highest averages were found for the axial (170,1 ± 38,2 m Zirkonzahn group/micro-CT) and occlusal (229,4 ± 49,0 m Cerec group/micro-CT) areas. Zirkonzahn group showed the UI closest to the ideal. Conclusion. The marginal adaptation and internal fit parameters of the 4 tested CAD-CAM systems were within clinically acceptable levels.